Women who to care victims of violence, women harassed at chilean psychosocial programs - Matamala Pizarro, José (2022)
The results of a qualitative research were exposed, whose objective was to analyze and understand the manifestation of workplace harassment in women of Chilean psychosocial programs that provided care work to victims of violence. Sampling was done intentionally and for convenience. Semi-structured interviews were conducted with 10 women from psychosocial programs of SENAME and SERNAMEG. The content-thematic analysis was carried out for the constructed data. The results showed that the exposure to workplace harassment was stigmatizing, mainly perpetrated by harassment to work, faced preferably with individual defensive strategies. The working conditions were syndicated as the main causes of workplace harassment. It is concluded that it involved damage to mental health and the rights of the workers.